Foundations of topology - Patty, C. Wayne (Sudbury, Mass. : Jones and Bartlett Publishers, 2009)
Topology is a branch of pure mathematics that deals with the abstract relationships found in geometry and analysis. Written with the mature student in mind, Foundations of Topology, Second Edition, provides a user-friendly, clear, and concise introduction to this fascinating area of mathematics. The author introduces topics that are well motivated with thorough proofs that make them easy to follow. Historical comments are dispersed throughout the text, and exercises, varying in degree of difficulty, are found at the end of each chapter. Foundations of Topology is an excellent text for teaching students how to develop the skill to write clear and precise proofs.
Topological spacesp. 1 New spaces from old onesp. 63 Connectednessp. 109 Compactnessp. 131 The separation and countability axiomsp. 163 Special topicsp. 197 Metrizability and paracompactnessp. 245 The fundamental group and covering spacesp. 265 Applications of homotopyp. 301 Appendicesp. 315 Bibliographyp. 367 Indexp. 369 Table of Contents provided by Blackwell. All Rights Reserved..
Includes bibliographical references (p. 367-368) and index.
1
Keywords: Topology